Lower Permian stems as fluvial paleocurrent indicators of the Parnaíba Basin, northern Brazil - Capretz, Robson Louiz [UNESP]; Rohn, Rosemarie [UNESP] (Elsevier, 2013)
A comprehensive biostratinomic study was carried out with abundant stems from the Lower Permian Motuca Formation of the intracratonic Parnaíba Basin, central-north Brazil. The fossils represent a rare tropical to subtropical paleofloristic record in north Gondwana. Tree ferns dominate the assemblages (mainly Tietea, secondarily Psaronius), followed by gymnosperms, sphenophytes, other ferns and rare lycophytes. They are silica-permineralized, commonly reach 4 m length (exceptionally more than 10 m), lie loosely on the ground or are embedded in the original sandstone or siltstone matrix, and attract particular attention because of their frequent parallel attitudes. Many tree fern stems present the original straight cylindrical to slightly conical forms, other are somewhat flattened, and the gymnosperm stems are usually more irregular. Measurements of stem orientations and dimensions were made in three sites approximately aligned in a W-E direction in a distance of 27.3 km at the conservation unit Tocantins Fossil Trees Natural Monument In the eastern site, rose diagrams for 54 stems indicate a relatively narrow azimuthal range to SE. These stems commonly present attached basal bulbous root mantles and thin cylindrical sandstone envelopes, which sometimes hold, almost adjacent to the lateral stem surface, permineralized fern pinnae and other small plant fragments. In the more central site, 82 measured stems are preferentially oriented in the SW-NE direction, the proportion of gymnosperms is higher and cross-stratification sets of sandstones indicate paleocurrents mainly to NE and secondarily to SE. In the western site, most of the 42 measured stems lie in E-W positions. The predominantly sandy succession, where the fossil stems are best represented, evidences a braided fluvial system under semiarid conditions. The low plant diversity, some xeromorphic features and the supposedly almost syndepositional silica impregnation of the plants are coherent with marked dry seasons. Thick mudstones and some coquinites below and above the sandy interval may represent lacustrine facies formed in probably more humid conditions. The taphonomic history of the preserved plants began with exceptional storms that caused fast-flowing high water in channels and far into the floodplains. In the eastern site region, many tree ferns only fell, thus sometimes covering and protecting plant litter and leaves from further fragmentation. Assemblages of the central and western sites suggest that the trees were uprooted and transported in suspension (floating) parallel to the flow. Heavier ends of stems (according to their form or because of attached basal bulbous root mantle or large apical fronds) were oriented to upstream because of inertial forces. During falling water stage, the stems were stranded on riverbanks, usually maintaining the previous transport orientation, and were slightly buried. The perpendicular or oblique positions of some stems may have been caused by interference with other stems or shallow bars. Rare observed stems were apparently waterlogged before the final depositional process and transported as bedload. The differences of interpreted channel orientations between the three sites are expected in a braided fluvial system, considering the very low gradients of the basin and the work scale in the order of tens of kilometers. The mean direction of the drainage probably was to east and the flows apparently became weaker downstream. This study seems to provide reliable data for paleocurrent interpretations, especially considering areas with scarce preserved sedimentary structures. © 2013 Elsevier Ltd.
Keywords: Biostratinomy; Late Paleozoic; Paleoflora; Taphonomy; Tocantins; Tree ferns; bioindicator; environmental conditions; environmental gradient; flora; fossil record; gymnosperm; paleocurrent; Permian; sandstone; sedimentary structure; stem; Brazil; Parnaiba Basin; Equisetophyta; Filicophyta; Gymnospermae; Lycopodiophyta